New record of Padaeus trivittatus (Hemiptera: Pentatomidae) as a predator of the monarch butterfly Danaus plexippus (Lepidoptera: Nymphalidae) in Central Mexico - Bernal-Pichardo, Simona F.; Zarco-González, Martha M.; Monroy-Vilchis, Octavio (Revista Colombiana de Entomología, 2024)
Lepidoptera includes agricultural pests, pollinators, and bioindicators of the environment quality. Adults of Danaus plexippus (Lepidoptera: Nymphalidae) are preyed by some birds, and rodents; in its immature stages are preyed mainly by arthropod predators. Arthropod predation is a factor that decreases the survival of D. plexippus. Two adult males of Padaeus trivittatus (Hemiptera: Pentatomidae) were found preying on D. plexippus for the first time.